Religion, Lifestyle, and Identity Affirmation within Middle Class Malay Muslims in Pontianak of West Borneo - Nur Hamzah; Sangkot Sirait; Zulkipli Lessy (Graduate Program of Pontianak Institute of Islamic Studies, 2022)
This work aims at revealing the implications of modernization and improvement of the living standards of the middle-class Malay Muslim community in Pontianak City. The modern world has proven to affects the aspects of religion and culture of the people in the globe, including the Malay Muslims in Pontianak. This is based on research employing qualitative approach with the support of ethnographic activities. Observations and in-depth interviews were to support the data collection from middle-class Malay Muslims in Pontianak. The work suggests that the modernization and improvement of the social class of Pontianak Malay Muslims has changed their relationship to the Malay culture where they have become more selective towards existing customs and traditions. In addition, the increase in the living standards has in fact also increased the desire of Malay Muslims towards various efforts to affirm class identity. Modern Malay Muslims tend to addopt modern life style with the supports of Islamic teachings they practice in everyday life as they consider Islam as the foundation of their customs and traditions. The hegemony of modernity has penetrated the life of the Malay Muslims and influenced the characteristics of their religiousity and Malaydom to a more modernized style.